Fence. Volume six, Redemption - Pacat, C. S. (BOOM! Box, 2023)
"THE COMPETITION HAS BEEN RESET... EN GARDE! Return to the thrilling world of high-stakes, competitive fencing, with a brand new story featuring the beloved cast of characters from the original hit series. Are Seiji and Jesse really through? The rumors around Halverton, the prestigious fencing training camp, have spread like wildfire, but it's not long before a mystery fencer arrives--one who may finally pose a threat to the #1 spot. Will Seiji's unquenchable quest for rivalry take Nicholas' place? Where will his loyalty lie? And, when Seiji gets an up close and personal look into Nicholas' past and determination against adversity while preparing for the difficult road ahead and the State Championships, he'll have to confront a tempting thought... are they on... a date? New York Times and USA Today best-selling author C. S. Pacat (Dark Rise, Nightwing) and acclaimed cartoonist Johanna the Mad (Wynd) continue their winning streak with this on-point entry in the GLAAD Media Award-nominated series!"--Amazon.